Pengaruh Pemberian Tepung Larva Black Soldier Fly terhadap Persentase Giblet pada Ayam Broiler: The Effect of Black Soldier Fly Larvae Flour on the Percentage of Giblets in Broiler Chickens - Aindi Yunus Abollasing; Agustinus Konda Malik; Sutan Y. F. G. Dillak (Jurnal Peternakan Lahan Kering, 2023)
This study aims to examine the effect of black soldier fly larvae flour (Hermetia illucens) on the percentage of giblets (gimmels, liver, heart and spleen) in broiler chickens. Study using 96 day old broiler chickens. The experimental design used in this study was a Completely Randomized Design  with 4 treatments. Each replication containning 4 day old broiler chickens. The treatment given consisted of R0: 0% maggot flour + 6% fish meal, R1: 2% maggot flour + 4% fish meal, R2: 4% maggot flour + 2% fish meal, R3: 6% maggot flour + 0% fish flour. The research variable is giblet percentage. The results showed that the usage of black soldier fly larvae flour had no significant effect (P>0.05) on the percentage of giblets. Based on the results of the study it can be concluded that the addition of black soldier fly larvae flour up to 6% in the ration has no significant effect on the percentage of gizzards, liver, heart and spleen. Because the protein content and metabolic energy in each treatment were the same, the giblet weight had no real influence. Tujuan penlitian ini untuk mengkaji pengaruh pemberian tepung larva black soldier fly (Hermetia illucens) terhadap persentase giblet (rempela, hati, jantung dan limpa) pada ayam broiler. Penelitian ini menggunakan  96 ekor anak ayam broiler umur sehari. Rancangan percobaan yang dilakukan dalam penelitian ini menggunakan Rancangan Acak Lengkap dengan 4 perlakuan, 6 ulangan dan setiap ulangan terdapat 4 ekor anak ayam. Perlakuan yang diberikan terdiri dari R0: 0% tepung maggot  + 6% tepung ikan,  R1: 2% tepung maggot + 4% tepung ikan, R2: 4% tepung maggot + 2% tepung ikan, R3: 6% tepung maggot + 0% tepung ikan. Variabel penelitian adalah peresentase giblet yang meliputi persentase rammpela, hati, jantung dan limpa. Hasil penelitian menunjukkan bahwa pemberian tepung larva black soldier fly berpengaruh tidak nyata (P>0,05) terhadap persentase giblet pada ayam broiler. Berdasarkan hasil penelitian dapat disimpulkan bahwa penambahan tepung larva black soldier fly sampai level 6% dalam ransum berpengaruh tidak nyata terhadap persentase rempela, hati, jantung dan limpa,